Classroom Teachers' Strategies in Instilling the Value of Religious Tolerance Based on Islamic Teachings to Elementary School Students: A Case Study at SD Negeri 006 Bontang Utara - Vera Diana Yulita; Amir Pantitingan; Nasri Hamang; Abdul Halik (CV. Edujavare Publishing, 2026)
Religious tolerance is a fundamental character value that should be cultivated from elementary education, particularly in Indonesia's multicultural society. This study aims to analyze students' religious tolerance attitudes, identify teachers' strategies for internalizing tolerance values based on Islamic teachings, and examine the challenges and solutions encountered at SD Negeri 006 Bontang Utara. A qualitative descriptive case study approach was employed. Data were collected through participant observation, unstructured interviews, and documentation involving eight informants, including the principal, one Islamic Religious Education teacher, and six classroom teachers. Data were analyzed using the Miles and Huberman model, while trustworthiness was ensured through credibility, transferability, dependability, and confirmability. The findings indicate that students generally demonstrate passive tolerance, characterized by religion-based peer grouping and discriminatory behaviors that become more complex across grade levels. Teachers promote tolerance through role modeling, habituation, reflective discussions, project-based learning, heterogeneous grouping, and inclusive prayer activities. However, implementation remains fragmented due to exclusive family influences, limited teaching materials, and inconsistent teacher practices. The study recommends institutional guidelines, professional learning communities, and stronger school–parent collaboration to foster sustainable religious tolerance.